Xenopus paraxial protocadherin inhibits Wnt/β‐catenin signalling via casein kinase 2β - Ciprianidis, Anja; Wang, Yingqun; Weber, Dominik; Steinbeisser, Herbert (EMBO reports, 2012)
Xenopus paraxial protocadherin (PAPC) regulates cadherin‐mediated cell adhesion and promotes the planar cell polarity (PCP) pathway. Here we report that PAPC functions in the Xenopus gastrula as an inhibitor of the Wnt/β‐catenin pathway. The intracellular domain of PAPC interacts with casein kinase 2 beta (CK2β), which is part of the CK2 holoenzyme. The CK2α/β complex stimulates Wnt/β‐catenin signalling, and the physical interaction of CK2β with PAPC antagonizes this activity. By this mechanism, PAPC restricts the expression of Wnt target genes during gastrulation. These experiments identify a novel function of protocadherins as regulators of the Wnt pathway.